Diversity analysis in parental lines of winter oilseed rape (Brassica napus L.): DIVERSITY ANALYSIS IN PARENTAL LINES OF WINTER OILSEED RAPE (BRASSICA NAPUS L.) - MANOJ KUMAR; R K SINGH (Journal of Oilseeds Research, 2018)
Genetic diversity is essential for crop genetic improvement. Genetic diversity among breeding lines helps breeders in selecting parents for hybrid production with maximumheterosis and combining useful genes in a genetic background. Twenty five genotype of Brassica napus from different places of the country were evaluated to study the diversity pattern among the genotypes. The genotypes were grouped into six clusters. The distribution pattern indicated that maximum number of genotypes 8 was grouped into the cluster II followed by cluster IV (6), and cluster I (5). Cluster V had 3 genotypes, cluster VI contained 2 genotypes while cluster III had only one genotype. The mode of distribution of genotypes from different geographic regions into various clusters was at random, indicating no association between geographical distribution of genotypes and the genetic divergence. The inter cluster distance in most of the cases was higher than the intra-cluster distance, indicationg wider genetic diversity among the accessions of different groups. The maximum intracluster distance (7.158) was observed for cluster I, the minimum intra cluster distance (2.642) was observed for cluster VI. The genotypes of cluster III and cluster VI exhibited maximum inter cluster distance (30.102) indicating higher genetic divergence and revealed that the genotypes Neelam and Sheetal were more divergent. Thusthese genotypes may be used to produce superior hybrids and transgressive segregants with heterobeltiosis effects in rapeseed.